2D CoOOH Sheet-Encapsulated Ni2P into Tubular Arrays Realizing 1000 mA cm−2-Level-Current-Density Hydrogen Evolution Over 100 h in Neutral Water - Zhang, Shucong; Wang, Wenbin; Hu, Feilong; Mi, Yan; Wang, Shuzhe; Liu, Youwen; Ai, Xiaomeng; Fang, Jiakun; Li, Huiqiao; Zhai, Tianyou (Nano-micro letters, 2020)
Highlights The 2D CoOOH sheet-encapsulated Ni 2 P into tubular arrays electrocatalytic system with expediting mass transport, structural stability, and tuned electron was conceptually proposed. The designed electrocatalysts realize expectant 1000 mA cm −2 -level-current-density hydrogen evolution in neutral water for over 100 h. Water electrolysis at high current density (1000 mA cm −2 level) with excellent durability especially in neutral electrolyte is the pivotal issue for green hydrogen from experiment to industrialization. In addition to the high intrinsic activity determined by the electronic structure, electrocatalysts are also required to be capable of fast mass transfer (electrolyte recharge and bubble overflow) and high mechanical stability. Herein, the 2D CoOOH sheet-encapsulated Ni 2 P into tubular arrays electrocatalytic system was proposed and realized 1000 mA cm −2 -level-current-density hydrogen evolution over 100 h in neutral water. In designed catalysts, 2D stack structure as an adaptive material can buffer the shock of electrolyte convection, hydrogen bubble rupture, and evolution through the release of stress, which insure the long cycle stability. Meanwhile, the rich porosity between stacked units contributed the good infiltration of electrolyte and slippage of hydrogen bubbles, guaranteeing electrolyte fast recharge and bubble evolution at the high-current catalysis. Beyond that, the electron structure modulation induced by interfacial charge transfer is also beneficial to enhance the intrinsic activity. Profoundly, the multiscale coordinated regulation will provide a guide to design high-efficiency industrial electrocatalysts.